2009
DOI: 10.1590/s0103-05822009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Infecção hospitalar em Unidade de Terapia Intensiva Neonatal: há influência do local de nascimento?

Abstract: OBJETIVO: Analisar comparativamente a incidência e o perfil etiológico da infecção hospitalar em recém-nascidos (RN) de origem interna e externa, admitidos em Unidade de Terapia Intensiva Neonatal (UTIN). MÉTODOS: Estudo de coorte em RN internados na UTIN em 2002 e 2003. A vigilância epidemiológica das infecções hospitalares foi realizada prospectivamente, seguindo-se os métodos do National Nosocomial Infections Surveillance System. Compararam-se as características clínicas, demográficas, a incidência de infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
6
2
9
Order By: Relevance
“…The overall NI incidence rates reported in Brazilian NICUs of 30.6% 7 and 22% 8 are much higher than those observed in most studies in the United States (11.4%) 9 or Europe (2.5%) 10 .…”
Section: Resultscontrasting
confidence: 57%
“…The overall NI incidence rates reported in Brazilian NICUs of 30.6% 7 and 22% 8 are much higher than those observed in most studies in the United States (11.4%) 9 or Europe (2.5%) 10 .…”
Section: Resultscontrasting
confidence: 57%
“…(2)(3)(4)(5)(6) However, the proportion of positive blood cultures among the patients with sepsis (17.1%) was lower than the figures reported in the literature (18% to 65%). (6,7,20,21) The blood cultures from the three patients who died revealed Gram-negative bacteria, raising the possibility that these agents are associated with increased mortality. This finding agrees with CohenWolkowiez et al and Gordon et al, who found that increased mortality ranging from 19% to 24% was related to Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…and Enterobacter spp., were isolated most frequently. (3,6,12,(27)(28)(29) An American study assessing only late-premature children has demonstrated that S. aureus and E. coli are often present in blood cultures. (7) The cross-sectional and retrospective nature of this study is a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The research is particularly relevant in Brazil due to the high prevalence of E. coli in the country. Studies published by Freitas et al, (2012) and Pinheiro et al, (2009) mentioned neonatal infection rates between 28.5% and 30.6% for Grampositive and Gram-negative bacteria. The DNA amplification of E. coli by PCR is a sensitive, specific and easily performed technique, and does not require cell culture.…”
Section: Discussionmentioning
confidence: 99%